The Circadian Clock, Reward, and Memory - Albrecht, Urs (Frontiers in Molecular Neuroscience, 2011)
During our daily activities, we experience variations in our cognitive performance, which is often accompanied by cravings for small rewards, such as consuming coffee or chocolate. This indicates that the time of day, cognitive performance and reward may be related to one another. This review will summarize data that describes the influence of the circadian clock on addiction and mood-related behavior and put the data into perspective in relation to memory processes.